2019 International Conference on Electronics, Information, and Communication (ICEIC) 2019
DOI: 10.23919/elinfocom.2019.8706445
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric Analysis of Published Literature on Industry 4.0

Abstract: Research on Industry 4.0 was initiated in 2012. Since then, the term "Industry 4.0" has been widely used among researchers to further investigate the development of technologies in the related industry. Thus, the aim of this study is to analyze the scientific literature published in the field of Industry 4.0. Scopus database was utilized to collect all literature in Industry 4.0. Publish or Perish software was used to incorporate the obtained data, while VOSviewer was used for data visualization. SPSS and Micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 20 publications
0
25
1
1
Order By: Relevance
“…Bibliometric analysis is a spatial representation technique widely used in academic research because it allows the researcher to analyze large amounts of information with the help of specialized software. That also shows a panoramic perspective of a topic obtained, by knowing the trajectory, the main contributions, the relevant authors, the gaps in the literature, future research and the limitations of the subject among many other relevant information (Ahmi et al 2019, Durmuşoğlu & Çiftçi 2018, Muhuri et al 2019.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Bibliometric analysis is a spatial representation technique widely used in academic research because it allows the researcher to analyze large amounts of information with the help of specialized software. That also shows a panoramic perspective of a topic obtained, by knowing the trajectory, the main contributions, the relevant authors, the gaps in the literature, future research and the limitations of the subject among many other relevant information (Ahmi et al 2019, Durmuşoğlu & Çiftçi 2018, Muhuri et al 2019.…”
Section: Methodsmentioning
confidence: 98%
“…For this, technological competitiveness analyzed from 1975 to 2019 and the emerging technology trends that are part of I4.0 and I5.0 also included. For this, was performed a bibliometric analysis, a systematic review of the literature (SRL), and content analysis, as they are techniques that provide a clear understanding of scientific performance when evaluating the literature review and identifying the main contributions of a topic (Ahmi et al 2019, Cancian et al 2018, Yoon et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…(2019),Ahmi et al (2019),Raptis et al (2019),Hohmann and Posselt (2019),Rojas and Rauch (2019),Oztemel and Gursev (2020),Xu et al (2018),Factorachian and Kazemi (2020),Da Silva et al (2019),Muhuri et al (2019),Piccarozzi et al (2018),Turner et al (2019),Ben-Daya et al (2019),Winkelhaus and Grosse (2020),Cui et al (2020),Rossit et al (2019a, c),Kipper et al (2020),Nakayama et al (2020),Fatorachian and Kazemi (2018),Pinzone et al (2020),Manavalan and Jayakrishna (2019), Heged} us et al (2019), Cardin (2019), Schuh et al (2014), Yang et al Zhang et al (2018), Khakifirooz et al (2018), H€ ackel et al (2019), Rossit et al (2019b), Gru zauskas et al (2018), Romero-Silva and Hern andez-L opez (2020), Juh asz and B anyai (2018) 11.86 Model/Architecture Garrido-Hidalgo et al (2019), Monostori et al (2016), Bicocchi et al (2019), Singh et al (2019), Cimini et al (2020) 8.47 Hypothesis Salam (2019), Bag et al (2020), Buchi et al (2020) 5.08 Experimenting method O'Donovan et al (2019), Regal and Pereira (2019) 3.38 Case study Sicari et al (2019), Choi et al (2017) 3.38 Others (Less then 2 item Marinagi et al (2018), Li (2018), Qiu et al (2018), Thoben et al (2017), Klumpp et al (2019), Foidl and Felderer (2015), Tuptuk and Hailes (2018), Kang et al (2016), Chengula et al (2018), Da Silva et al (2019), Kusiak ((2018), Manavalan and Jayakrishna (2019), Marinagi et al (2018), H€ ackel et al (2019), Heged} us et al (2019), Raptis et al (2019), Bicocchi et al (2019), Qiu et al (2018), Factorachian and Kazemi (2020), Tuptuk and Hailes (2018), Kang et al (2016), Monostori et al (2016), Cohen et al (2019) M2: Human factors Pinzone et al (2020), Li (2018), Cardin (2019), Da Silva et al (2019), Piccarozzi et al (2018), Winkelhaus and Grosse (2020), Klumpp et al (2019), Buchi et al (2020), Qu et al (2019), Yang et al (2019), Singh et al (2019) M3: cyber-physical industrial system Cimini et al (2020), Monostori et al (2016), Thoben et al (2017), Rossit et al (2019a, b, c), Pinzone et al (2020), Khakifirooz et al (2018), Cardin (2019), Schuh et al (2014), Hohmann and Posselt (2019), Rojas and Rauch (2019), Muhuri et al (2019), Romero-Silva and Hern andez-L opez (2020), Kusiak (2018), Juh asz and B anyai (2018) M4: Quality management/ Maintenance Foidl and Felderer (2015), Ben-Daya et al (2019), Turner et al (2019), Singh et al (2019), Cohen et al (2019) Logistics(L) L1: Warehousing Singh et al (2019), Ben-Daya et al (2019), Winkelhaus and Grosse (2020). Gru zauskas et al (2018) L2: Procurement/ Purchases Factorachian and Kazemi (2020...…”
mentioning
confidence: 99%
“…Thus, under the documents type, conference papers are collections of papers presented in conferences and eventually published in journals as articles. Moreover, some conference papers were also published in either book chapters or conference proceedings although the original document type is the conference paper (Ahmi, Elbardan, & Ali, 2019). As stated at the beginning of this section, this study found only four types of documents: articles, conference paper, book chapter and reviews.…”
Section: Document and Source Typesmentioning
confidence: 91%